2015
DOI: 10.1158/1078-0432.ccr-14-1905
|View full text |Cite
|
Sign up to set email alerts
|

Stromal CD8+ T-cell Density—A Promising Supplement to TNM Staging in Non–Small Cell Lung Cancer

Abstract: Purpose: Immunoscore is a prognostic tool defined to quantify in situ immune cell infiltrates, which appears to be superior to the tumor-node-metastasis (TNM) classification in colorectal cancer. In non-small cell lung cancer (NSCLC), no immunoscore has been established, but in situ tumor immunology is recognized as highly important. We have previously evaluated the prognostic impact of several immunological markers in NSCLC, yielding the density of stromal CD8 þ tumor-infiltrating lymphocytes (TIL) as the mos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
239
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(266 citation statements)
references
References 31 publications
25
239
1
1
Order By: Relevance
“…increased CD+8 tiLs have been associated with a better prognosis in many solid neoplasms, including colorectal, melanoma and triplenegative breast carcinoma (4). This study showed that CD8+ tiLs have a significant prognostic effect, as the patients with high CD8+ tiLs gave a partial response to therapy and had a better survival more than those with low CD8+ tiLs; this goes with Donnem et al (13) who found that the stromal CD8+ tiLs density was a strong independent prognostic factor for PFS and OS.…”
Section: Resultssupporting
confidence: 65%
“…increased CD+8 tiLs have been associated with a better prognosis in many solid neoplasms, including colorectal, melanoma and triplenegative breast carcinoma (4). This study showed that CD8+ tiLs have a significant prognostic effect, as the patients with high CD8+ tiLs gave a partial response to therapy and had a better survival more than those with low CD8+ tiLs; this goes with Donnem et al (13) who found that the stromal CD8+ tiLs density was a strong independent prognostic factor for PFS and OS.…”
Section: Resultssupporting
confidence: 65%
“…Only two of the previously published similar studies included validation cohorts (12,13). In the study by Donnem et al, one training set and three external validation sets with a total of 797 patients were examined (12).…”
mentioning
confidence: 99%
“…Only two of the previously published similar studies included validation cohorts (12,13). In the study by Donnem et al, one training set and three external validation sets with a total of 797 patients were examined (12). In this study, density of CD8+ T cells was assessed only in stroma as our group previously found stromal CD8+ density (14), rather than within the epithelial cancer cell nests to have significantly stronger prognostic impact with respect to DFS, disease-specific survival (DSS), and OS.…”
mentioning
confidence: 99%
“…CD8+ TIL density has also been evaluated in early stage lung cancer. In a retrospective study of 797 pathologic stage I-IIIA NSCLC, stromal CD8+ TIL density was independently prognostic of disease free survival, disease specific survival, and OS (all P<0.001) (19).…”
Section: Cd8+ Tilsmentioning
confidence: 98%